A computational algorithm coupled with a particle selection routine for the simulation of the Bond locked-cycle test. (January 2022) - Camalan, Mahmut
Graphical abstract: Highlights: Bond index estimation is labor-intensive, time consuming and sensitive to errors. An algorithm is presented to simulate Bond locked-cycle grinding test. The algorithm is fast, yielding reproducible indices with negligible errors. The algorithm predicts the grinding behavior at consecutive cycles. The algorithm estimates slightly higher Bond indices. Abstract: The Bond's Equation is commonly used to predict the size-reduction energy in tumbling mills. The calculation of the Bond Equation requires the Bond Index, which is estimated through the results of the locked-cycle grinding tests. However, the tests are time-consuming, labor-intensive, and sensitive to errors. An algorithm is alternatively proposed to simulate the locked-cycle Bond tests by executing cycles of successive breakage events on non-randomly selected particles. The algorithm can yield reproducible Bond work indices fast with negligible computational errors. The algorithm's applicability was validated against the experimental Bond tests on different ore samples. The results show that the algorithm can predict the grinding behavior of the mill hold-up at successive cycles. However, the simulated grindabilities are lower than the experimental ones, causing the algorithm to estimate slightly higher work indices as compared to the experimental indices. There is no sufficient data to conclude if such differences are because of (i) poor scaling of the breakage events, (ii) sampling/sieving errors, or (iii) varying grinding kinetics.